Psychological behavior patterns and coping with menopausal symptoms among users and non-users of hormone replacement therapy in Finnish cohorts of women aged 52–56 years - Jaana Jalava-Broman; Niina Junttila; Lauri Sillanmäki; Juha Mäkinen; Päivi Rautava (Elsevier Ireland Ltd, 2022)
Objective: To identify subgroups of women who differ with respect to self-evaluated stress, hostility, optimismand sense of coherence, and to identify differences, if any, in whether these subgroups use or do not use hormonereplacement therapy (HT).
Study design and methods: This time-trend study is based on the Finnish national HeSSup study, in which na-tionwide cohorts of Finnish women aged 52–56 years randomly selected in 2000 (n = 1321) and in 2010(n = 1389) responded to postal questionnaires related to four psychological behavior patterns.
Main outcome measures: Relationships between psychological behavior patterns (stress, hostility, optimism andsense of coherence) and how menopausal symptoms are experienced and how this relates to the use of HT.
Results: The proportion of HT users was higher among those with more stress and hostility and less optimism andsense of coherence than among those low in stress and hostility and high in optimism and sense of coherence.
Conclusions: Differences in psychological behavior patterns influence the perception of menopausal symptomsand the use of HT. When the treatment of women at menopause is planned, psychological behavior patternsshould be considered, as these reflect the ability to cope with menopausal symptoms.